2000
DOI: 10.1111/j.1346-8138.2000.tb02171.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Photodynamic and Sonodynamic Therapy on Experimental Skin Squamous Cell Carcinoma in C3H/HeN Mice

Abstract: We studied a combination of photodynamic therapy (PDT) and sonodynamic therapy (SDT) for improving tumoricidal effects in a transplantable mouse squamous cell carcinoma (SCC) model. Two sensitizers were utilized: the pheophorbide-a derivative PH-1126, which is a newly developed photosensitizer, and the gallium porphyrin analogue ATX-70, a commonly used sonosensitizer. Mice were injected with either PH-1126 or ATX-70 i.p. at doses of 5 or 10 mg/kg.bw. At 24 (ATX-70) or 36 hr (PH-1126) (time of optimum drug conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 43 publications
1
70
0
3
Order By: Relevance
“…Kusuzaki et al reported acridine orange PDT followed by radiotherapy suppressed tumor growth of osteosarcoma-bearing mice [15]. Jin et al also suggested the use of a combination of PDT and sonodynamic therapy improved the tumoricidal effects in squamous cell carcinoma in mice [9]. Okunaka et al reported the pulsed wave laser showed a higher effect of PDT than the continuouswave laser [23].…”
Section: Discussionmentioning
confidence: 97%
“…Kusuzaki et al reported acridine orange PDT followed by radiotherapy suppressed tumor growth of osteosarcoma-bearing mice [15]. Jin et al also suggested the use of a combination of PDT and sonodynamic therapy improved the tumoricidal effects in squamous cell carcinoma in mice [9]. Okunaka et al reported the pulsed wave laser showed a higher effect of PDT than the continuouswave laser [23].…”
Section: Discussionmentioning
confidence: 97%
“…70 The mechanism of PDT action is reasonably well understood, whereas that of USAT is less well characterized. The hypothesis on the enhanced Tables 6 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used sonosensitizers were hematoporphyrine (Hp) and its derivatives (HpD). However, they were liable to cause severe photo-dermatitis and difficult to be used in clinical practice extensively [5]. In this regard, it becomes increasingly important to explore novel sonosensitizers with fewer side effects.…”
Section: Introductionmentioning
confidence: 99%